Management at a time of change annual conference, Bournemouth, 9-13 June 1986. (Thomas Telford, 1986)
Providing access to engineering content from the past, this is the proceedings of the Association of Municipal Engineers' annual conference held in 1986.
Keywords: Municipal engineering -- Congresses.; elektronické knihy; electronic books